(3EOGQI GdJShjb (B/s - (3GdUjQaj, eMeOs ((3GdbGgQI(B: s (3eDSSI WjHI ddfTQh GdJhRjY(B, s, 2005)
(3JLO aj gPG GdcJGH (B: (3GdEOGQI hGdJShjb , GdJNWjW GdJShjbj ,GdJfXje GdJShjbj , GdbQGQGJ GdJShjbI , GdJhLjg GdJShjbj , GdQbGHI hGdeQGLYI Ydi GdfTGW GdJShjbjs
(3GdeQGLY U(B.325s
Keywords: (3EOGQI GdJShjbs